Die DDR-Zensur und die Selbstzensur in den Augen der Autoren des ,Prenzlauer Berges' - Bettin, Monika (Studia Germanica Posnaniensia, 2018)
The artist scene at ,,Prenzlauer Berg“ in the Eastern part of Berlin was one of the few possibilities for artists in the GDR to escape the onmipresent pressure by the state. This article mainly shows the conception of the artist themselves. After some years of German unity it is evident that the scene has sunk into insignificance, in the first place this is probably because it is no longer needed as a means to grapple with the system.